Combating ‘Galamsey’ in Ghana and Its Implications for Ghana-China Relations: An Assessment - Nyamekye-Acquah, M.K. (University of Ghana, 2018)
This study was an assessment of Government of Ghana’s anti-galamsey activities on Ghana-China diplomatic relations. The focus of the study was to determine whether anti-galamsey activities of the government have had any strain on the diplomatic relations between the two countries. The study relied on both primary and secondary sources of data for analysis. Widespread damage to Ghana’s environment, water bodies, farmlands and wildlife due to “galamsey”, a local referent for illegal mining, had become a grave concern. While those involved in “galamsey” includes both Ghanaians and foreigners, the introduction of sophisticated equipment and use of dangerous chemicals by Chinese migrants in the extraction of Gold through illegal means had resulted into a “galamsey” narrative directed heavily at the Chinese. With widespread media reportage on the issue mostly highlighting damages to the environment, water bodies, conflicts and deaths, the government was forced to act, hence the decision to combat “galamsey” of which the majority of foreigners involved are Chinese migrants. While this decision was welcomed by many, other experts feared the consequences of this decision on Ghana-China diplomatic relations due to the latter’s economic contribution to the development of Ghana. Findings from the study revealed that Ghana-China diplomatic relations have not been significantly impacted by Government of Ghana’s ‘anti-galamsey’ activities and that these activities have no current or future negative implications on the diplomatic exchanges between Ghana and China and that the current state of Sino-Ghana relations remains friendly.
MA.
Keywords: Galamsey; Ghana-China Relations